INTERNALISASI KONSEP CYCLE RELATION MODEL PADA KOMUNITAS AGAMA LOKAL DI INDONESIA : (Perspektif Sosial, Ekonomi dan Politik Pada Kepercayaan Towani Tolotang, Aluk Todolo dan Patuntung di Sulawesi Selatan) - Damirah; Darwis; Abd. Hamid; Musmulyadi (LIPI Press, 2022)
This research is qualitative research using an interpretive paradigm with a phenomenological approach to see and find out the relationship between the community or local religious adherents and the government in the realization of the cycle relation model concept. Research data was obtained by in-depth interviews and observations. The results of the study show that people who follow local religions in South Sulawesi (Ammatoa, Towani Tolotang, Aluk Todolo) still carry out their local religious traditions until now, even though they already have their respective official religions. The results of the study also show that their social, economic and political life is also very good, they live side by side well with other general people. Regarding the relationship between the government, based on the results of the study, it shows that the relationship that exists between the community and the government is very good where the community carries out its obligations to the government and the government gives the community rights as citizens